Submucosal Tunneling Endoscopic Resection for the Management of Heterotopic Pancreas With Cystic Degeneration. Issue 7 (9th July 2020) - Almazan, Erik; Runge, Thomas; Li, Qing Kay; Ngamruengphong, Saowanee
ABSTRACT: Heterotopic pancreas is pancreatic tissue present outside of the normal location of the pancreas. In the presence of cystic degeneration, heterotopic pancreas is clinically significant because of the symptoms it causes and its physical resemblance to cancerous growth. A diagnosis of heterotopic pancreas is achieved with the aid of various endoscopic techniques for tissue removal. Submucosal tunneling endoscopic resection has proven successful for the resection of gastric subepithelial masses. We present a 53-year-old woman undergoing submucosal tunneling endoscopic resection for the resection of a subepithelial gastric cyst caused by heterotopic pancreas with cystic degeneration.